Storm rising [large type] - Kendig, Ronie (The book of the wars, 2019)
"Once lost, the Book of the Wars has resurfaced, holding ancient secrets--and dangers. Former Navy SEAL Leif Metcalfe is assigned to capture the text, but a Bulgarian operative snatches it, determined to secure her freedom. When a series of storms erupt, they must form an alliance to thwart disaster"--